2004
DOI: 10.1088/0953-8984/16/40/003
|View full text |Cite
|
Sign up to set email alerts
|

The oxygen isotope effect on the in-plane penetration depth in cuprate superconductors

Abstract: Abstract. Muon-spin rotation (µSR) studies of the oxygen isotope (16 O/ 18 O) effect (OIE) on the in-plane magnetic field penetration depth λ ab in cuprate high-temperature superconductors (HTS) are presented. First, the doping dependence of the OIE on the transition temperature T c in various HTS is briefly discussed. It is observed that different cuprate families show a similar doping dependence of the OIE on T c . Then, bulk µSR, low-energy µSR, and magnetization studies of the total and site-selective OIE … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
79
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 79 publications
9
79
0
Order By: Relevance
“…In our theory the strong spin-fluctuation pairing is induced by the kinematic interaction which is absent in the weak correlation limit as in FLEX approximation, and therefore, the EPI plays only a secondary role in the d-wave pairing. A strong EPI in polaronic effects observed in the oxygen isotope effect on the in-plane penetration depth in cuprates [84] may be irrelevant for the pairing mediated by the d-wave partial harmonic of the EPI [85] as confirmed by a weak isotope effect on T c in the optimally doped cuprates.…”
Section: Comparison With Previous Theoretical Studiesmentioning
confidence: 85%
“…In our theory the strong spin-fluctuation pairing is induced by the kinematic interaction which is absent in the weak correlation limit as in FLEX approximation, and therefore, the EPI plays only a secondary role in the d-wave pairing. A strong EPI in polaronic effects observed in the oxygen isotope effect on the in-plane penetration depth in cuprates [84] may be irrelevant for the pairing mediated by the d-wave partial harmonic of the EPI [85] as confirmed by a weak isotope effect on T c in the optimally doped cuprates.…”
Section: Comparison With Previous Theoretical Studiesmentioning
confidence: 85%
“…In particular, close to optimal doping the OIE on T c is almost zero [1, 2, 3], while the OIE on λ ab (0) is still substantial [7,8,9,10]. With decreasing doping both OIE's on T c and λ ab (0) increase and, for highly underdoped materials, even exceed the value of the BCS isotope exponent α BCS Tc = 0.5 [2,4,5,7,9,10]. In order to obtain a more global view of cuprate superconductors a detailed study of the isotope dependence of magnetic quantities is needed.…”
Section: Oxygen Isotope (mentioning
confidence: 99%
“…16 O/ 18 O) effects (OIE's) on various physical quantities, including among others the transition temperature T c , the in-plane magnetic penetration depth λ ab (0), the pseudogap temperature T * , and the spin-glass temperature T g , were observed which cannot be explained by standard BCS theory [1,2,3,4,5,6,7,8,9,10,11,12]. For instance, it was found that the OIE's on T c and λ ab (0) are strongly doping dependent [1,2,3,4,5,6,7,8,9,10].…”
Section: Oxygen Isotope (mentioning
confidence: 99%
See 2 more Smart Citations